Mathematical model of livestock and wildlife: Predation and competition under environmental disturbances - Laguna, Maria Fabiana; Abramson, Guillermo; Kuperman, Marcelo Nestor; Lanata, Jose Luis; Monjeau, Jorge Adrian (Elsevier Science, 2015)
Fil: Laguna, Maria Fabiana. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina